في مراقبة المحكمة الإدارية لدستورية القوانين عن طريق الدفع - بن حسن, عصام (جامعة الوادي University of Eloued, 2019)
ملخص: في الوقت الذي كان للقاضي العدلي (العادي) الأسبقية التاريخية في الفصل في دستورية القوانين عن طريق الدفع، استقر فقه قضاء المحكمة الإدارية منذ السنوات الأولى لبداية عملها على أن مراقبة دستورية القوانين لا تندرج ضمن الاختصاص القضائي للقاضي الإداري عملا بنظرية القانون الحاجب أو الستار التشريعي. ثم اتجهت المحكمة الإدارية إلى تغيير موقفها بعد حل المجلس الدستوري سنة 2011، حيث أخذت على عاتقها مسؤولية مراقبة دستورية القوانين عن طريق الدفع وذلك في ظل غياب هيكل يضمن دستورية القوانين، بل أنها وبعد إنشاء الهيئة الوقتية لمراقبة دستورية مشاريع القوانين، ذهبت إلى أبعد من ذلك بإقرارها للقاضي الإداري إمكانية النظر في دستورية الأحكام التشريعية التي لم يسبق للهيئة الوقتية لمراقبة دستورية مشاريع القوانين الحسم في دستوريتها، وهو ما سيتم تناوله في هذا المقال مع الوقوف على الأسانيد التي اعتمدتها المحكمة الإدارية للإقرار باختصاصها في مراقبة دستورية القوانين عن طريق الدفع. Abstract: While the common law judges has had the historical precedence in determining the constitutionality of laws since 1987, the jurisprudence of Administrative Courts has settled upon the idea that the monitoring of the constitutionality of laws does not fall within the jurisdiction of the administrative judge since its early years, Although they have acknowledged for themselves the authority to control the constitutionality of administrative decisions that are not based on a legal provision that forms a barrier between them and the Constitution according to the theory of obstructive law or the legislative shield. The Administrative Court then changed its stance after the dissolution of the Constitutional Council in 2011. It assumed the responsibility of monitoring the constitutionality of laws through exception, in the absence of a structure that guarantees the constitutionality of laws. And went even further than that by acknowledging to the administrative judge the possibility of reconsidering the constitutionality of legal provisions that were not reviewed by the provisional organism of Constitutionality control of bills. This is the matter that will be addressed in this article, along with the arguments adopted by the Administrative Court to recognize its competence in monitoring the constitutionality of laws through exception. Abstract. key words: Tunisian administrative judge; The exception of the unconstitutionality of laws; The control of the constitutionality of laws through exception the provisional organism of Constitutionality control of bills.
Keywords: القاضي الإداري التونسي ; الدفع بعدم دستورية القوانين ; مراقبة دستورية القوانين عن طريق الدفع ; نظرية القانون الحاجب ; الهيئة الوقتية لمراقبة دستورية مشاريع القوانين; Tunisian administrative judge ; The exception of the unconstitutionality of laws ; The control of the constitutionality of laws through exception the provisional organism of Constitutionality control of bills